Koe Mata Ae Liaki Ako. The Face of Truancy. - Holliday, Laiha (Auckland University of Technology, 2025)
Truancy is a growing phenomenon in New Zealand. Māori and Pasifika whānau are overrepresented in the truancy data. This research listens to the voices of non-attending students to hear and understand their school journeys. Exploring the backgrounds and experiences of Māori and Pasifika students through talanoa may help us better understand the barriers that prevent them from attending school and reaching educational success. Increased understanding of school attendance, or lack of it, will assist in improving the paths to success for Māori and Pasifika students in the future. Addressing our alarming truancy rates requires addressing the unique challenges and needs of our most disadvantaged Māori and Pasifika young people. The voices of these six truants might be understood to represent the impact of systemic failures and social neglect. Hearing first-hand accounts of their educational journey has provided a more holistic and empathetic understanding of these young people's challenges; hearing their voices has allowed a more profound understanding and justified interpretivism as a research methodology. Many Māori and Pasifika young people fail to successfully navigate the New Zealand education system. The barriers to educational attendance and success are diverse. Through talanoa with the students, this research established the themes of absent parents; violence in the home; relationships with teachers; mental health issues; and drugs. The six absentee Māori and/or Pasifika young people revealed parents who were absent in their lives; they felt that their parents had abandoned them, they felt responsible for their siblings, and they were opting to distance themselves from their parents to protect themselves from constant disappointment regarding their parents. The talanoa revealed violence in their homes and lives from a very young age. The talanoa highlighted that the young people's attitudes at school mirrored the attitudes at home, and the violence from home started to bleed into violence at school. Of interest, the talanoa exposed a dislike for mothers, but fathers were exonerated and held in high regard, even though they were the aggressors. The young people spoke in depth about their dislike and disrespect of their teachers, reciprocating the attitudes they felt they were receiving from their teachers. Mental health issues were prominent across four of the journeys recounted by the participants.